Exploring the Influence of Lifestyle Factors on Consumer Purchasing Behavior in Online Stores - Shaputra, Sandro Theo (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
This research investigates the influence of lifestyle on consumer purchasing behavior in online stores. Through a mixed-methods approach combining quantitative surveys and qualitative interviews, the study examines the interplay between demographic characteristics, online shopping habits, and lifestyle factors. Findings reveal that higher-income individuals tend to shop online more frequently and spend more per transaction, while those with a high technological affinity prefer certain online platforms. Social media engagement also plays a significant role in influencing purchasing decisions, particularly in product categories like beauty and personal care. Implications for online retailers, marketers, and policy-makers are discussed, along with suggestions for future research. Overall, this research contributes to our understanding of online shopping dynamics and provides insights for stakeholders navigating the digital marketplace.